Comparison of average estimated metabolic rates for styrene in previously exposed and unexposed groups with pharmacokinetic modelling. Issue 9 (September 1996) - Wang, Y; Kupper, L L; Löf, A; Rappaport, S M
Abstract : OBJECTIVE: To understand whether previous styrene exposure increases the human liver's ability to convert styrene into styrene oxide. METHODS: The hypothesis was tested that the average linear metabolic rate constant kappa was the same in both exposed and unexposed groups, when the exposed group comprised people with a history of styrene exposure and the unexposed group had no exposure. In an experimental chamber, these two groups of subjects were exposed to a concentration of 80 ppm styrene for two hours. A three compartment pharmacokinetic model was used to define kappa. Based on large sample theory, the comparison of estimated mean values of kappa in the exposed and unexposed groups was shown to be equivalent to a comparison of the estimated mean values of the hepatic clearance X in the two groups. A method was developed to estimate X for each subject in both groups from the subject's height, weight, and estimated asymptotic styrene decay constant alpha. Here, alpha was estimated individually from observed blood concentrations over time when sufficient time had elapsed after the controlled exposure. RESULTS: The proposed methodology of comparing the estimated mean values of kappa in exposed and unexposed groups reduced the number of specific physiological variables involved to three, all of which were estimable from data based on simple direct measurements. In contrast, other methods based on pharmacokinetic models usually involved many variables that were non-estimable on an individual basis. Consequently, statistical comparisons were impossible. These methods were applied to analyse previously published data on the time course of styrene concentrations in arterial blood of subjects in both exposed and unexposed groups. A Wilcoxon non-parametric rank sum test with the individually estimated X values was used, and no significant difference in the means of X in the two groups was found. CONCLUSION: The linear metabolic rate constant kappa for humans is probably not altered by previous exposure to styrene. This result is in agreement with some experimental studies on animals. However, in the data analysis, it was noted that the number of subjects in each group was small (6-7) and that the styrene concentration data did not exactly reflect true behaviour of asymptotic decay. Further studies are still needed to draw more definitive conclusions.